Congenital anterior urethral valves and diverticula: Diagnosis and management in six cases - Rawat Jiledar; Khan Tanvir; Singh Sarita; Maletha Madhukar; Kureel Shivnarain (Wolters Kluwer Medknow Publications, 2009)
Background: Anterior urethral valves (AUVs) are rare congenital anomalies causing lower urinary tract obstruction in children. Although they are referred to as valves, these obstructive structures often occur in the form of a diverticulum. The urethra in these cases shows saccular or bulbar dilatation known as anterior urethral diverticulum (AUD). They typically occur where there is a defect in the corpus spongiosum, leaving a thin-walled urethra. This segment of the urethra balloons out during voiding, simulating a mass that is sometimes visible along the ventral wall of the penis. The swelling is fluctuant and urine dribbles from the meatus on compression. The present study highlights the clinical approach in identifying the condition and its treatment options, especially for those, presenting with urethral diverticula. Materials and Methods: We have studied children with congenital anterior urethral valves and diverticula. Six patients of AUVs with diverticula were admitted during the period of 2000-2007 and were prospectively evaluated. The mean age of presentation was 16 months (15 days to 4 years). Straining at micturition and a palpable penile swelling were the most common presenting features. The diagnosis was established by voiding cystourethrogram (VCUG) and supported by ultrasonography (USG). All patients were treated with single-stage open surgical excision except one who died preoperatively due to urosepsis. Initial lay opening of the penoscrotal urethra and delayed repair were done in one patient. Results: The surgical outcome was successful in all but one patient, who died of delayed presentation with severe back pressure changes, urinary ascitis and urosepsis. On long-term follow-up, all patients demonstrated good stream of urine. The renal functions were normal and the patients had no evidence of urinary infections. Conclusion: We propose that, the patients of AUVs, if not excessively delayed for treatment are otherwise well in terms of general condition as opposed to patients of posterior urethral valves. The diagnosis is easily established by VCUG and the severity is revealed by a sonogram. Open surgical excision is the method of choice for patients with a urethral diverticulum; however, cystoscopic fulguration is also feasible in selected patients. The outcome is excellent with minimal morbidity and mortality.